Association of CT-based diagnosis of sarcopenia with prognosis and treatment response in patients at risk of malnutrition – A secondary analysis of the Effect of early nutritional support on Frailty, Functional Outcomes, and Recovery of malnourished medical inpatients Trial (EFFORT) trial. Issue 2 (February 2023) - Baumgartner, Annic; Olpe, Tobias; Griot, Stephanie; Mentil, Nicole; Staub, Nathalie; Burn, Felice; Schindera, Sebastian; Kaegi-Braun, Nina; Tribolet, Pascal; Hoess, Claus; Pavlicek, Vojtech; Bilz, Stefan; et al.
Summary: Background & aim: CT-derived measures of muscle mass may help to identify patients with sarcopenia. We investigated the prognostic significance of CT-derived sarcopenia and muscle attenuation with nutritional markers, clinical outcomes and response to nutritional support in medical in-patients at nutritional risk. Method: Within this secondary analysis of the randomized-controlled Effect of early nutritional support on Frailty, Functional Outcomes, and Recovery of malnourished medical inpatients Trial (EFFORT) comparing individualized nutritional support with usual care nutrition in medical inpatients, we investigated associations of CT-based sarcopenia and muscle attenuation at the level L3 with different nutritional and clinical outcomes, and the response to the nutritional intervention. The primary composite endpoint was adverse clinical outcome within 30 days of hospital admission. Results: We included 573 of 2028 EFFORT patients with available CT scans, of which 68.4% met the CT-based definition of sarcopenia and 72.9% had low muscle attenuation. In multivariate analysis, low skeletal muscle index was associated with higher nutritional risk (coefficient per NRS class −0.94 (95%CI −1.87 to −0.01) p = 0.049) and higher risk for adverse clinical outcomes (adjusted odds ratio 1.59 (95% CI 1.06 to 2.38), p = 0.024). Low muscle attenuation was also associated with adverse clinical outcome (adjusted odds ratio 1.67 (95%CI 1.08 to 2.58), p = 0.02). Nutritional support tended to be more effective in reducing mortality in non-sarcopenic patients compared to patients with CT-based sarcopenia (p for interaction 0.058). Conclusions: Within a population of medical patients at nutritional risk, CT-based sarcopenia and muscle attenuation were associated with several nutritional parameters and predicted adverse clinical outcomes. Information from CT scans, thus may help to better characterize these patients, and may be helpful in guiding therapeutic interventions.